Features and benefi ts of using new forms of antibiotics with improved pharmacokinetic properties - А. L. Vertkin; M. M. Shamuilova; G. Yu. Knorring (Лечащий Врач, 2022)
Antibiotics remain one of the most popular classes of drugs used in modern medicine. The high medical and social significance of infections, their tendency to epidemic spread, places high demands on the effectiveness and safety of antibiotic therapy. Limitations in the development of new antibiotics, the emergence of new infectious outbreaks, and the growing problem of antibiotic resistance make the optimization of dosing regimens and the use of antibacterial drugs relevant. The article considers the possibilities and effectiveness of the use of modern forms of antibiotics with improved pharmacokinetic properties. The opinion that existed in the medical environment for a long time about the greater effectiveness of parenteral forms of antimicrobial drugs has recently been refuted. The innovative technology for creating dispersible tablets proposed at the beginning of the 21st century proved the comparability of both therapeutic concentrations of an antibiotic when using dispersible forms of an antibiotic and parenteral forms of administration, and the clinical effectiveness of their use. The manufacturing technology of dispersible forms consists in the fact that the tablet is formed from a plurality of microspheres consisting of a filler and an active substance, which creates conditions for protecting the microspheres from the influence of the acidic environment of the stomach and ensures the release of the active substance when exposed to bicarbonates in the intestine, i.e. in the zone of maximum antibiotic absorption. All this contributes to a higher bioavailability of the drug compared to tablet forms, and also provides more uniform dosing and, as a result, predictability of pharmacokinetics. This dosage form differs from traditional oral dosage forms in higher bioavailability of active substances, comparable to injectables, as well as a number of advantages that improve compliance. The improved pharmacokinetic profile of these forms of antibiotics is intended to provide higher clinical efficacy and tolerability and help reduce antibiotic resistance.